Імітація реалістичного ігрового супротивника за допомогою штучного інтелекту на основі моделі GPT TEXT-DAVINCI-003 - Калініченко, О. Ю. (ХНУРЕ, 2024)
This thesis investigates the application of artificial intelligence to model a realistic game opponent. The main focus is on analyzing a variety of artificial intelligence approaches and models in order to develop strategies for creating the most realistic bot behavior in the game space. In addition, the paper pays attention to the importance of proper selection of cues, which play a key role in ensuring interactivity and dynamics of the gameplay. The results of the study reveal strategic approaches to creating an adversary that can effectively adapt to different game scenarios and provide players with an exciting and unpredictable gaming experience.
Keywords: імітація; ігровий супротивник; штучний інтелект; GPT; OpenAI